Empirical Analysis on the Impact of Management Efficiency and Watch Loans on the Bankruptcy Rate of Community Banks in Tanzania: A Random Effect Model Approach - Yohana, Hapho; Gwahula, Raphael (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
This paper analyses the impact of management efficiency and watch loans on the bankruptcy rate of community banks in Tanzania, for the period ranging from 2006 to 2021. In Tanzania, for the period starting from 2017 to 2019, seven community banks were closed by the Regulator while others were being merged to increase their operational efficiency and going concern. The failure of these banks raised a lot of concerns among banks’ stakeholders including private sector, the government and the general public. The study used archival reviews as one of the tools for secondary data collection in quantitative research where panel data were collected from community banks and the Bank of Tanzania publications. The employed sample size was 11 community banks, with a total of 176 observations. The panel data analysis has been conducted using statistical software (Stata) with the random effect model being used to generate regression results as one of the statistical models for panel data analysis. The research findings indicated significant negative correlations between the explanatory variables, namely, management efficiency and watch loan ratios with bankruptcy rates as computed using the Altman’s model approach specific for developing countries. This paper contributes to the contagion theory by arguing that not only bank runs that causes bank failure, but also there are other factors such as; management inefficiency and high level of watch loans as justified by the theory of market structure and asymmetric information theory. Further, for the purpose of diminishing bankruptcy rate of community banks, the study recommends adequate credit management policy in terms of proper credit appraisal systems and strong corporate governance policy, which reduce level of watch loans and operational costs.